PEMAKNAAN BUDAYA, PESONA DAKWAH DAN DAMPAK SOSIAL: MENELISIK TRADISI SAHUR-SAHUR DI MEMPAWAH KALIMANTAN BARAT - Wibowo, Basuki; Syaifulloh, Muhammad; Dediansyah, Agus; Hidayat, Sahid; Lubis, Ali Akhbar Abaib Mas Rabbani (AL-TAHRIR, 2024)
This study highlights the sahur-sahur tradition in Mempawah, which serves not only as a form of cultural heritage. The study aims to explore the sahur-sahur tradition beyond its understanding of culture, examining its appeal in da'wah and its positive implications on the social environment. Conducted through a descriptive-exploratory approach supported by oral history, the study gathers data from literature reviews, observations, and in-depth interviews with key figures, including custodian of the Amantubillah Palace, religious leaders, community figures, and administrators of Galaherang Kreasindo in Mempawah. The findings reveal that the sahur-sahur tradition encompasses religious, communal, and cultural dimensions, creating a rich cultural heritage. This tradition also carries a unique da'wah appeal, having evolved into a sahur festival that features diverse activities, such as sermons, religious studies, and artistic performances. Its social implications are evident in fostering community solidarity, promoting cultural tourism and stimulating creativity.